Pengaruh Managerial Entrenchment, Struktur Modal, Profitabilitas, Dan Likuiditas Terhadap Kualitas Laba - Eggita Wahyu Amalia; Justita Dura (LPPM ISNJ Bengkalis, 2022)
Managerial entrenchment is a crucial activity because it is closely related to the company's operational control. This study aimed to assess the effect of managerial entrenchment, capital structure, profitability, and liquidity on earnings quality. This study uses a quantitative approach. The study population is companies members of the blue-chip index listed on the Indonesia Stock Exchange for the 2019-2020 periods. Sampling uses the purposive sampling technique to obtain a sample of 27 companies. Data was collected using a documentation approach that came from the company's official website and the Indonesia Stock Exchange. Multiple linear regression analysis was used as a test approach. The study results reveal that managerial entrenchment, profitability, and liquidity have no effect on earnings quality, but capital structure affects earnings quality. This study can help the company's internal and external parties to expand information transparency and create good quality profits.